2004
DOI: 10.1086/420850
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of SecretedAspergillus fumigatusProteases in Disruption of the Actin Fiber Cytoskeleton and Loss of Focal Adhesion Sites in Infected A549 Lung Pneumocytes

Abstract: Aspergillus fumigatus is an opportunistic pathogenic fungus that predominantly infects the respiratory system. Penetration of the lung alveolar epithelium is a key step in the infectious process. The cytoskeleton of alveolar epithelial cells forms the cellular basis for the formation of a physical barrier between the cells and their surroundings. This study focused on the distinct effects of A. fumigatus on the actin cytoskeleton of A549 lung pneumocytes. Of the 3 major classes of cytoskeletal fibers--actin mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 26 publications
0
87
0
1
Order By: Relevance
“…CF from the prtT deletion strain exhibits reduced killing of lung epithelial cells and lysis of erythrocytes. Our previous studies have shown that secreted A. fumigatus proteases disrupt A549 cell actin fibers and focal adhesions, leading to cell detachment and death (15). Those results suggested that A. fumigatus breaches the alveolar epithelial cell barrier by secreting proteases that act together to disorganize the actin cytoskeleton and destroy cell attachment to the substrate by disrupting focal adhesions.…”
Section: Vol 77 2009mentioning
confidence: 94%
See 2 more Smart Citations
“…CF from the prtT deletion strain exhibits reduced killing of lung epithelial cells and lysis of erythrocytes. Our previous studies have shown that secreted A. fumigatus proteases disrupt A549 cell actin fibers and focal adhesions, leading to cell detachment and death (15). Those results suggested that A. fumigatus breaches the alveolar epithelial cell barrier by secreting proteases that act together to disorganize the actin cytoskeleton and destroy cell attachment to the substrate by disrupting focal adhesions.…”
Section: Vol 77 2009mentioning
confidence: 94%
“…The following evidence implicates secreted A. fumigatus proteases in virulence: (i) secreted A. fumigatus proteases induce proinflammatory cytokine release in infected macrophages and epithelial cells, thereby alerting the immune system (14); (ii) infected lung epithelial cells also undergo protease-dependent changes to the actin cytoskeleton, leading to cell peeling and death (15,36); (iii) proteases are secreted in vivo during infection, and protease-specific antisera show labeling of mycelium in the lungs of patients and experimentally infected animals (22); (iv) loss of elastase protease activity in mutagenized strains of A. fumigatus has been correlated with decreased virulence in vivo (16); and (v) mice intratracheally injected with purified ALP1 protease showed a marked degree of lower respiratory tract destruction (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is not used by all microorganisms, so it is considered as an important virulence factor. Some fungal species are known to be capable of invading mammalian cells in vitro and in vivi, but few studies have described the invasion process [11,19,22,[63][64][65].…”
Section: Invasion Processmentioning
confidence: 99%
“…The genome of A. fumigatus contains several genes most likely coding for proteases (Rementeria et al, 2005), leading to the assumption that the need for nutrients could be satisfied from protein degradation. Moreover, during lung infection it has been demonstrated that A. fumigatus indeed produces several proteases (Kogan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%